Identification and fine‐mapping of RppCML496, a major QTL for resistance to Puccinia polysora in maize. Issue 1 (9th November 2020) - Lv, Meng; Deng, Ce; Li, Xueying; Zhao, Xiaodi; Li, Huimin; Li, Zhimin; Tian, Zhiqiang; Leonard, April; Jaqueth, Jennifer; Li, Bailin; Hao, Junjie; Chang, Yuxiao; et al.
Abstract: Southern corn rust (SCR), which is caused by the fungal pathogen Puccinia polysora Underw, is a prevalent foliar disease in maize. Breeding for resistant cultivars is a desirable way for the efficient control of this disease. To identify quantitative trait loci (QTL) for conferring resistance to SCR, a recombinant inbred population including 138 lines (RILs) derived from the SCR‐resistant line CML496 and susceptible line Lx9801 was evaluated for phenotypic reaction to SCR in three trials in two locations over 2 years. The population was genotyped with the maize 9.4K SNP Genotyping Array marker platform. A total of 3 QTL were mapped on chromosomes 6, 9 and 10, respectively. One major QTL on chromosome 10 (bin 10.00/10.01), RppCML496, was consistently detected across environments, which explained 43–78% of the total phenotypic variation. Using a fine mapping strategy, we delimited RppCML496 to an interval of 128 Kb. Genome mining of this region suggests two candidate genes, and a NBS‐LRR gene is the promising one for RppCML496 against SCR. The tightly linked molecular markers developed in this study can be used for molecular breeding of resistance to SCR in maize. Core Ideas: Southern corn rust is a prevalent foliar disease in maize. One major QTL, RppCML496, was detected on the short arm of chromosome 10. Fine‐mapping resolved a 128 Kb interval containing two candidate genes.